Gastrointestinal parasites of owl monkeys (Aotus Azarai Azarai) in the Argentinean Chaco - Perea Rodriguez, Juan Pablo (2010)
Fil: Perea Rodriguez, Juan Pablo. Florida International University; Estados Unidos.